The secrets of animal flight - Bishop, Nic, 1955- (Boston : Houghton Mifflin, 1997)
Explains how birds, bats, and insects fly, presenting photos and anatomical diagrams.
Includes bibliographical references.
Wilson's Children.
Elem. School Library Collection.
School Library Journal starred.
5.6
K-3
Keywords: Animal flight -- Juvenile literature; Animal flight; Animal flight; Animal flight